Gynecomastia: Clinical evaluation and management - Cuhaci, Neslihan (Medknow Publications & Media Pvt Ltd, 2014)
Gynecomastia is the benign enlargement of male breast glandular tissue and is the most common breast condition in males. At least 30% of males will be affected during their life. Since it causes anxiety, psychosocial discomfort and fear of breast cancer, early diagnostic evaluation is important and patients usually seek medical attention. Gynecomastia was reported to cause an imbalance between estrogen and androgen action or an increased estrogen to androgen ratio, due to increased estrogen production, decreased androgen production or both. Evaluation of gynecomastia must include a detailed medical history, clinical examination, specific blood tests, imaging and tissue sampling. Individual treatment requirements can range from simple reassurance to medical treatment or even surgery. The main aim of any intervention is to relieve the symptoms and exclude other etiological factors.